Assimilate OpenAI. (Pragmatic AI Solutions, 2022)
Assimilate OpenAI Learn OpenAI weekly by example This video course will show you how to build real-world applications with OpenAI's pre-trained cutting edge AI models. Topics Covered Include: 1.0- Introduction to OpenAI, a one hour exploration of many of the cutting edge AI models and projects you can build in the playground. Learning Objectives Learn the OpenAI platform Build a real-world application using OpenAI's pre-trained models Explore the types of projects you can build with OpenAI: Q&A, Summarization, NLP, SQL translation, Python to natural language, etc. Tweaking generated Python code from OpenAI inside of Github CodeSpaces and Cloud9 Additional Popular Resources Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn * AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.